Operating system concepts : international student version. - Silberschatz, Abraham, ....-; Gagne, Greg, ....-; Galvin, P. B., ....- (Hoboken : Wiley, 2010)
Operating System Concepts, now in its eighth edition, continues to provide a solid theoretical foundation for understanding operating systems. The eighth edition includes more coverage of the most current topics in the rapidly changing fields of operating systems and networking, including open-source operating systems. The use of simulators and operating system emulators is incorporated to allow operating system operation demonstrations and full programming projects. The text also includes improved conceptual coverage and additional content to bridge the gap between concepts and actual implementations. New end-of-chapter problems, exercises, review questions, and programming exercises help to further reinforce important concepts. New to this edition: > over 15 new programming exercises that emphasize processes, threads, shared memory, process synchronization, and networking > added coverage of virtual machine scheduling and multi-threaded, multi-core architectures, as well as livelock issues > significantly updated coverage of virtual machines, as well as multi-core CPUS, the GRUB boot loader, and operating system debugging > added discussion of mutual exclusion locks, priority inversion > additional coverage of iSCSI, volumes, ZFS pools, PCIX PCI Express, and Hyper-Transport
Keywords: Besturingssystemen